2018
DOI: 10.1016/j.brainresbull.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into mitochondrial molecular targets of iron-induced neurodegeneration: Reversal by cannabidiol

Abstract: Evidence has demonstrated iron accumulation in specific brain regions of patients suffering from neurodegenerative disorders, and this metal has been recognized as a contributing factor for neurodegeneration. Using an experimental model of brain iron accumulation, we have shown that iron induces severe memory deficits that are accompanied by oxidative stress, increased apoptotic markers, and decreased synaptophysin in the hippocampus of rats. The present study aims to characterize iron loading effects as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 71 publications
1
41
0
Order By: Relevance
“…A previous study indicated that CBD attenuates the imbalance between Bcl-2/Bax, upregulating the anti-apoptotic protein Bcl-2, which in turn maintains the integrity of the outer mitochondrial membrane, in an animal model of multiple sclerosis 46 . In agreement, we have previously demonstrated that CBD protects against mitochondrial injury 13,30 , converging to prevent the activation of the intrinsic apoptotic pathway. Using a model of HD, Valdeolivas and coworkers 47 have suggested the involvement of CB1 and CB2 cannabinoid receptors as well as receptor-independent actions in the neuroprotective effects of a CBD-enriched botanical extract.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A previous study indicated that CBD attenuates the imbalance between Bcl-2/Bax, upregulating the anti-apoptotic protein Bcl-2, which in turn maintains the integrity of the outer mitochondrial membrane, in an animal model of multiple sclerosis 46 . In agreement, we have previously demonstrated that CBD protects against mitochondrial injury 13,30 , converging to prevent the activation of the intrinsic apoptotic pathway. Using a model of HD, Valdeolivas and coworkers 47 have suggested the involvement of CB1 and CB2 cannabinoid receptors as well as receptor-independent actions in the neuroprotective effects of a CBD-enriched botanical extract.…”
Section: Discussionsupporting
confidence: 89%
“…Since mitochondria are the main source of ROS, they are expected to become an important target of oxidative damage, which could explain functional alterations in these organelles in pathological conditions 45 . Moreover, mitochondria play a key role in regulating the intrinsic apoptotic pathway, and there is evidence indicating that iron affects mitochondrial homeostasis 13,30 , thus supporting the concept that iron effects are most pronounced in the intrinsic pathway. Nonetheless, more studies on the effects of iron on the extrinsic pathway are warranted.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…CBD restores the basal levels of hippocampal dynamin‐1‐like protein (DNM1L), caspase 3, and synaptophysin in animals with cell damage subsequent to iron loading . These effects are also associated with reversion of the iron‐induced mitochondrial deoxyribonucleic acid (mtDNA) deletions, the decreased epigenetic modulation of mtDNA, as well as restauration of the mitochondrial ferritin levels and succinate dehydrogenase activity . According to these studies, CBD induces epigenetic effects that results in the restauration of the normal cellular function and neuroprotection.…”
Section: Cannabidiol May Act On Unconventional Central and Peripheralmentioning
confidence: 99%
“…122 These effects are also associated with reversion of the iron-induced mitochondrial deoxyribonucleic acid (mtDNA) deletions, the decreased epigenetic modulation of mtDNA, as well as restauration of the mitochondrial ferritin levels and succinate dehydrogenase activity. 123 According to these studies, CBD induces epigenetic effects that results in the restauration of the normal cellular function and neuroprotection. Epigenetic effects induced by CBD hold promise as a future therapeutic strategy for drug-resistant epilepsy.…”
Section: On Unconventional Central and Peripheral Targets To Control mentioning
confidence: 99%